The Greek Version of the Mild Behavioral Impairment Checklist (MBI-C): Psychometric Properties in Mild Cognitive Impairment Due to Alzheimer’s Disease - Efthalia Angelopoulou; Evangelia Stanitsa; Maria Hatzopoulou; Akylina Despoti; Niki Tsinia; Vasiliki Kamtsadeli; Marina Papadogiani; Vasilis Kyriakidis; Sokratis Papageorgiou; John D. Papatriantafyllou (Brain Sciences)
Background/Objectives: Mild behavioral impairment (MBI) is an early marker of Alzheimer’s disease (AD) and other neurodegenerative diseases, often preceding cognitive decline. The MBI Checklist (MBI-C) is a 34-item tool designed to detect MBI. This study aimed to assess the psychometric properties of the Greek version of the MBI-C and its ability to differentiate patients with mild cognitive impairment due to AD (MCI-AD) from cognitively unimpaired older adults (healthy participants, HPs). Methods: A total of 181 participants (104 MCI-AD, 77 HPs) were recruited from the Third Age Day Care Center IASIS (2019–2023), accompanied by a close informant. Participants underwent neuropsychological assessment [Mini-Mental State Examination (MMSE), Addenbrooke’s Cognitive Examination-Revised (ACE-R)], and informants completed the MBI-C. Internal consistency was evaluated using Cronbach’s α and known-group validity was assessed via comparing MBI-C between the MCI-AD and HPs groups. Diagnostic accuracy was determined via receiver operating characteristic (ROC) analysis. Results: The Greek MBI-C showed excellent internal consistency (Cronbach’s α = 0.899). Among its domains, impulse dyscontrol demonstrated the highest reliability (α = 0.901), whereas decreased motivation (α = 0.564) and abnormal perception/thought content (α = 0.617) exhibited lower reliability. MBI-C total and domain scores were significantly higher in patients with MCI-AD than HPs (p < 0.001). The area under the curve (AUC) was 0.871 (optimal cutoff = 9.5), indicating excellent diagnostic performance. Conclusions: Overall, the Greek MBI-C has strong psychometric properties for MCI-AD. Sociocultural factors might influence symptom identification and reporting, particularly in the domains of decreased motivation and abnormal perception/thought content. Future research should investigate its predictive value for dementia conversion and its applicability to other populations, including individuals with subjective cognitive decline and non-AD causes of MCI.